2015
DOI: 10.1016/j.explore.2015.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Semen Quality Improvement in a Man with Idiopathic Infertility Treated with Traditional Korean Medicine: A Case Report

Abstract: Approximately 45-50% of the cases of infertility result from deficiencies associated with male factors, and 30-45% of these deficiencies are idiopathic. A standardized approach for the treatment of idiopathic male infertility remains elusive. In Korea, male infertility has been treated with either acupuncture, herbal remedies, or pharmacopuncture. We report a case of male idiopathic infertility in which the patient's semen quality improved through traditional Korean medicine (TKM) therapies, which was evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 14 publications
0
15
0
1
Order By: Relevance
“…Infertility is a common disorder affecting some one in seven couples, and subfertility has become a markedly increasing problem in affluent countries, with the most commonly identified cause attributed to 'male factor' ( 1 – 3 ). Several scientific studies have suggested that a decrease in male fertility is frequently associated with smoking, which may cause a decrease in semen quality ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Infertility is a common disorder affecting some one in seven couples, and subfertility has become a markedly increasing problem in affluent countries, with the most commonly identified cause attributed to 'male factor' ( 1 – 3 ). Several scientific studies have suggested that a decrease in male fertility is frequently associated with smoking, which may cause a decrease in semen quality ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Also, garlic can repair and protect the DNA of the sperm, in addition to sperm maturation through vitamins C, B, E, which are its potent antioxidants (53). Approximately 45%-50% of infertility has a male cause, but nevertheless, 30-45% is due to idiopathic causes (54). Typically, infertility in men is indicated by oligozoospermia, asthenozoospermia, or teratozoospermia and varicocele (55).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, Lycium barbarum juice significantly increased antioxidant biomarkers in the serum of healthy adults after continuous consumption for 30 days (Amagase, Sun, & Borek, ). A case study found that a 13% and 4% increase of sperm motility and normal sperm morphology, respectively, in a man with idiopathic infertility after treatment with a traditional Korean medicine containing Lycium barbarum (Jo, Lee, Lee, & Jerng, ).…”
Section: Introductionmentioning
confidence: 99%
“…30 days (Amagase, Sun, & Borek, 2009). A case study found that a 13% and 4% increase of sperm motility and normal sperm morphology, respectively, in a man with idiopathic infertility after treatment with a traditional Korean medicine containing Lycium barbarum (Jo, Lee, Lee, & Jerng, 2015).…”
mentioning
confidence: 99%